A style option for rotated objects in TeX - Rahtz, S; Barroca, L (TeX Users Group, 1992)
This article documents a LaTeX style option, 'rotating.sty', which perform all the different sorts of rotation one might like, including complete figures, within the context of a PostScript driver.